Smoking Cessation in Saudi Arabia: A Comprehensive Review - Bayan Emad Alabbad et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Smoking remains a significant public health challenge in Saudi Arabia, with high prevalence rates among adults and young populations. Despite national efforts to curb smoking, such as awareness campaigns, taxation policies, and smoking cessation programs, the rates of success in quitting remain suboptimal. This review explores the current smoking cessation strategies in Saudi Arabia, the barriers to success, and recommendations for improving outcomes. Recent studies emphasize the need for culturally tailored interventions, improved healthcare provider training, and expanded use of pharmacotherapy and behavioral counseling. Received Date: November 05, 2024 Accepted Date: November 26, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/286 https://doi.org/10.5281/zenodo.14529221